OPTIMIZATION OF THE INTERNATIONAL COMMITTEE OF THE RED CROSS TOWARDS THE PROTECTION OF HUMAN RIGHTS OF THE INTERNATIONAL COMMUNITY - Subakdi; Setiyawati, Marina Ery (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The International Committee of the Red Cross or ICRC is an international organization that carries out humanitarian missions in the health sector. The ICRC helps international countries that are in criminal conflict to protect the human rights of civilians affected by the conflict. The purpose of this study is that the authors hope to find out the ICRC's optimization of the protection of human rights in the international community. This research uses a literature study research method on the ICRC's optimization of the protection of human rights of the international community in countries that have been given assistance by the ICRC before.